Development of wafer-level-packaging technology for simultaneous sealing of accelerometer and gyroscope under different pressures. (23rd August 2016) - Aono, T; Suzuki, K; Kanamaru, M; Okada, R; Maeda, D; Hayashi, M; Isono, Y
Abstract: This research demonstrates a newly developed anodic bonding-based wafer-level-packaging technique to simultaneously seal an accelerometer in the atmosphere and a gyroscope in a vacuum with a glass cap for micro-electromechanical systems sensors. It is necessary for the accelerometer, with a damping oscillator, to be sealed in the atmosphere to achieve a high-speed response. As the gyroscope can achieve high sensitivity with a large displacement at the resonant frequency without air-damping, the gyroscope must be sealed in a vacuum. The technique consists of three processing steps: the first bonding step in the atmosphere for the accelerometer, the pressure control step and the second bonding step in a vacuum for the gyroscope. The process conditions were experimentally determined to achieve higher shear strength at the interface of the packaging. The packaging performance of the accelerometer and gyroscope after wafer-level packaging was also investigated using a laser Doppler velocimeter at room temperature. The amplitude at the resonant frequency of the accelerometer was reduced by air damping, and the quality factor of the gyroscope showed a value higher than 1000. The reliability of the gyroscope was also confirmed by a thermal cyclic test and an endurance test at high humidity and high temperature.